One Axis, Two Faces: The Shared Biology of PMS and Migraine - Makieła, Michalina; Koziak, Weronika; Makieła, Marta; Bętkowska, Aleksandra; Kornacka, Agata; Zając, Aleksandra; Szostak, Kamila; Tomaka, Rafał; Worobiej, Daniel; Dudek, Stanisław (Quality in Sport, 2025)
Premenstrual Syndrome (PMS) and migraine are two clinically distinct but biologically intertwined conditions that disproportionately affect individuals of reproductive age. Both disorders are characterized by cyclical patterns tied to hormonal fluctuations—most notably the abrupt withdrawal of estrogen and changes in progesterone levels during the luteal phase. Recent research reveals a convergence of underlying mechanisms, including dysregulation of the serotonergic and GABAergic systems, neurovascular instability, and heightened inflammatory responses. This narrative review explores how a shared neuroendocrine axis may drive the manifestation of both PMS and migraine, resulting in overlapping physical and emotional symptoms. By examining these interconnected pathways, we aim to illuminate opportunities for integrated diagnostic strategies and multimodal therapeutic approaches that consider the full scope of hormonal, neurological, and immune interactions. Understanding the "one axis, two faces" framework could be the key to more effective and individualized care.